(untitled) (Advancements in Homeopathic Research, 2022)
Migraine is a primary headache disorder characterized by recurrent headaches that are moderate to severe. Typically, the headaches affect one half of the head, are pulsating in nature, and last from a few hours to 3 days. Associated symptoms may include nausea, vomiting, and sensitivity to light, sound, or smell.